HEV-associated neuralgic amyotrophy: a multicentric case series - Bannasch, Johannes H.; Berger, Benjamin; Schwartkop, Claus-Peter; Berning, Marco; Goetze, Oliver; Panning, Marcus; Fritz-Weltin, Miriam; Trendelenburg, George; Gelderblom, Mathias; Lütgehetmann, Marc; Stute, Fridrike; Horvatits, Thomas; et al. (Pathogens, 2021)
Background: Neuralgic amyotrophy (NA) has been described as a possible extrahepatic manifestation of hepatitis E virus (HEV) infection. Usually, HEV-associated NA occurs bilaterally. The clinical characteristics determining the course of HEV-associated NA have still not been defined. Methods: In this retrospective multicentric case series, 16 patients with HEV-associated NA were studied and compared to 176 HEV patients without NA in terms of their age, sex, and ALT levels. Results: Neither gender distribution (75% vs. 67% male) nor age (47 vs. 48 years median) differed significantly between the NA patients and controls. Eight NA patients (50%) presented with bilateral involvement—seven of these had right-side dominance and one had left-side dominance. Thirteen cases (81%) were hospitalized. Eight of these patients stayed in hospital for five to seven days, and five patients stayed for up to two weeks. The time from the onset of NA to the HEV diagnosis, as well as the diagnostic and therapeutic proceedings, showed a large variability. In total, 13 (81%) patients received treatment: 1/13 (8%) received intravenous immunoglobulins, 8/13 (62%) received glucocorticoids, 3/13 (23%) received ribavirin, and 6/13 (46%) received pregabalin/gabapentin. Patients with ages above the median (47 years) were more likely to be treated (p = 0.001). Conclusion: HEV-associated NA causes a relevant morbidity. In our case series neither the type of treatment nor the time of initiation of therapy had a significant effect on the duration of hospitalization or the course of the disease. The clinical presentation, the common diagnostic and therapeutic procedures, and the patients’ characteristics showed large variability, demonstrating the necessity of standardized protocols for this rare but relevant disease.
Gesehen am 23.08.2021